The Influence of Candle Painting Activities on Development Fine Motor Skill of Children Aged 4-5 years in Al-Qur'an Kindergarten Jauharul Wathon Moaro Jambi - Mayola Sapitri; Asih Nur Ismiatun; Akhmad Fikri Rosyadi (UIN Mataram, 2024)
This research aims to determine the effect of wax painting activities on the fine motor development of children aged 4-5 years at Al-Qur'an Kindergarten, Jauharul Wathon Muaro Jambi. This type of research is quantitative with experimental methods. The design used in this research is Pre-Experimental Design in the form of One Group Pretest Posttest Design. The population in this study was 29 children and the sample in this study was 15 children. The sampling technique used in this research was an observation sheet. The data analysis techniques used in this research are normality test, homogeneity test and hypothesis test. Based on the discussion of the results of the research carried out, it can be concluded that there is an influence of wax painting activities on the fine motor development of children aged 4-5 years at Al-Qur'an Kindergarten, Jauharul Wathon Muaro Jambi. This is proven by testing the t test hypothesis that tcount (52.316) > t table (2.145), so Ho is rejected and Ha is accepted. From the effect size calculation using Cohen's formula, there is a result of 7.11, which means the magnitude of the influence of candle painting activities on the fine motor development of children aged 4-5 years at Al-Qur'an Kindergarten, Jauharul Wathon, Muaro Jambi, which is at a distance of >1 to strong interpretation (Strong effect). Keywords: Candle Painting Activities, Fine Motor Development, Early Childhood Aged 4-5 Years.